Downregulation of membrane type-matrix metalloproteinases in the inflamed or injured central nervous system - Toft-Hansen, Henrik (BioMed Central, 2007)
BACKGROUND: Matrix metalloproteinases (MMPs) are thought to mediate cellular infiltration in central nervous system (CNS) inflammation by cleaving extracellular matrix proteins associated with the blood-brain barrier. The family of MMPs includes 23 proteinases, including six membrane type-MMPs (MT-MMPs). Leukocyte infiltration is an integral part of the pathogenesis of autoimmune inflammation in the CNS, as occurs in multiple sclerosis and its animal model experimental autoimmune encephalomyelitis (EAE), as well as in the response to brain trauma and injury. We have previously shown that gene expression of the majority of MMPs was upregulated in the spinal cord of SJL mice with severe EAE induced by adoptive transfer of myelin basic protein-reactive T cells, whereas four of the six MT-MMPs (MMP-15, 16, 17 and 24) were downregulated. The two remaining MT-MMPs (MMP-14 and 25) were upregulated in whole tissue. METHODS: We used in vivo models of CNS inflammation and injury to study expression of MT-MMP and cytokine mRNA by real-time RT-PCR. Expression was also assessed in microglia sorted from CNS by flow cytometry, and in primary microglia cultures following treatment with IFNγ. RESULTS: We now confirm the expression pattern of MT-MMPs in the B6 mouse, independent of effects of adjuvant. We further show expression of all the MT-MMPs, except MMP-24, in microglia. Microglia isolated from mice with severe EAE showed statistically significant downregulation of MMP-15, 17 and 25 and lack of increase in levels of other MT-MMPs. Downregulation of MT-MMPs was also apparent following CNS injury. The pattern of regulation of MT-MMPs in neuroinflammation showed no association with expression of the proinflammatory cytokines TNFα, IL-1β, or IFNγ. CONCLUSION: CNS inflammation and injury leads to downregulation in expression of the majority of MT-MMPs. Microglia in EAE showed a general downregulation of MT-MMPs, and our findings suggest that MT-MMP levels may inversely correlate with microglial reactivity.